Sediment yield accumulation at reservoir (Batang Ai Dam) - Sharifah Azmin, Wan Hossen. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Modified Universal Soil Loss (MUSLE) which is one of the empirical prediction techniques was used to estimate the annual soil loss at catchment area of Batang Ai dam. The catchment area is about 1200km² and the rainfall data was analyzed for 20 years duration which from 1989 until 2008. The MUSLE parameters such as the soil erodibility factor, K was obtained from the soil map which contains the description of soil erodibility classification based on the symbol of series on the map. Moreover, the values of slope length and steepness factor, LS are taken from one point to another point of Batang Ai reservoir. The runoff coefficient, C and crop management factor, CP based on the references and determi ned by visual observation of the study area. The obtained K value is 0.438 whereas LS value is 0.782. In addition, the value of C and CP is 0.015 and 0.010 respectively. Maximum and minimum annual values of sediment yield obtained using the method is 70,22 4 tons per year and 42,620 tons per year. Besides, the relationship between rainfall and sediment yield obtained was y = 17.12x – 320.3 with r² = 0.950 . This study is important to describe the soil erosion condition of the study area and give an idea about erosion and sediment yield which is a serious problem that needs more attention from the responsible party. The result of this study can be used in order to improve the implementation of the land management system at the study area.